Pengaruh Heat Treatment Setelah Water Cooling pada Baja ST 60 Terhadap Sifat Mekanik - Herlingga, Muhammad (Jurnal sosial dan sains, 2025)
This study aims to determine the effect of heat treatment and quenching processes on the hardness value of ST 60 steel. ST 60 steel is a medium carbon steel with a carbon content of 0.564% and manganese content of 0.697% which has hard and wear-resistant properties. The research method uses an experimental approach with heat treatment process at 950°C temperature with holding time variations of 20 and 50 minutes, followed by quenching with water media. Hardness testing was performed using the Vickers method with an indentation load of 5 kgf at 5 different points for each specimen. The results showed that the hardness value of ST 60 steel increased significantly after heat treatment. Maximum hardness was achieved at 20 minutes holding time with a value of 734.521 HVN, increasing 137% compared to the initial material which had a hardness of 309.308 HVN. At 50 minutes holding time, the hardness obtained was 615.924 HVN. The increase in hardness is caused by the formation of martensite structure due to rapid cooling which causes carbon atoms to be trapped in supersaturated solid solution. This research shows that holding time variation affects the hardness value, where the optimal holding time is 20 minutes to achieve maximum hardness in ST 60 steel. , ,, ,